Análise de viabilidade do uso de nuvens computacionais oportunistas - Oliveira, Kawe Ramon Borgydark de (2013)
Cloud computing is a technology which is increasingly gaining market. Used by large and small companies, it is able to provide elastic and flexible access to network environments and computational resources providers, meeting the users' necessities who needs applications which run on large-scale environments. It also enables the best use of the performance of computational resources, avoiding laziness. On this essay, it is proposed a cloud opportunistic approach, which allows the use of idle resources in an available computing infra structure, enabling the creation of a richer network environment, able to provide more resources for hardware and software compared to a common environment.